Meditation, A Highly Powerful Tool to Enhance the Productivity and Happiness of Life in Modern World - Maiti, Ratikanta (International Journal of Bio-resource and Stress Management, 2017)
In the present day world, everybody is quite busy for their own work and running behind it to achieve the desired goal. However, the process is complex and does not always lead to smooth success. Topsy-turvy of life creates pain, agony, sorrow and stress. Deep stress brings about so many health problems which had strong negative impact on one’s generative capacity. It has detrimental effect both on mental and physique. Meditation, the so called process for connecting people with spirit through cosmic forces; practiced often by the monks, become skillful technique for relieving stress in contemporary time. Meditation centers are providing in-house meditational training. Virtual training is also available on-net. This unique article focused on the different available techniques of meditation and a lucid description how to practice that. Further, it reflected its influence on quality life and well being. Article described about meditation for beginners while also for expert on ‘Transitional Meditation’ and Chakra Meditation. Moreover, influence of nature, sound of rippling water, chirping of covey of birds, warmth of morning sun and in tune with traditional instrumental music has well described. Further, it was stated that this practice could connect us with our spirit, soul and universe. Therefore it concluded as meditation is a highly powerful technology to enhance the productivity, and happiness in mankind.